Tutkimustiedon hyödyntäminen kestävän hyvinvoinnin lähteenä: Tuloksia yliopistomaailman valmiuksista edistää löydöksien käyttöönottoa; Exploitation of Research Findings as a Source of Well-being - Annu Kotiranta; Antti-Jussi Tahvanainen (The Research Institute of the Finnish Economy (ETLA), 2018)
– In Finland, universities have the explicit mandate to support the transformation of high-quality knowledge into profitable business, as well as to promote the creation of new businesses and workplaces within the boundaries of their so-called third mission. This report looks at how Finnish universities perform in the task. The results point at a clear lack of dedicated resources. The underlying reason is systemic: performance is not linked to incentives in the form of public university funding. Currently, resources for the implementation of the third mission are largely obtained via competition from external sources, endangering the continuity of the technology transfer function and creating disincentives to invest in its development. The lack of incentives is echoed among researchers: Nearly half of the scientists who, according to their own view, have made economically valuable findings state they do not find the time to promote their exploitation. The report proposes several remedies: (1) the performance of universities in their third mission needs to be metered. (2) These metrics need to be linked to earmarked public university funding; (3) Individual-level metrics concerning the exploitation of their findings should encourage researchers and promote their academic careers. In order to support more rapid cultural change, universities could (4) recruit professors directly from the business world; and (5) set up cooperative, joint laboratories with industry in their respective strategic research areas.
Keywords: O31; O32; O33; O38; O43; O52; D02; I23; I25; I26; I28; 330; Technology transfer; Third mission; Commercialization; University; Higher education; Hochschule; Technologietransfer; Kommerzialisierung; Bewertung; Finnland